Development Free Fall Motion Teaching Aid With Proximity Sensor - Endah Istiqomah; Umi Pratiwi; Ashari Ashari (Jurnal Inovasi Pendidikan Sains (JIPS), 2022)
The use of manual teaching aid causes inaccurate results. This study aims to realize a valid and effective free fall motion teaching aid based on proximity sensors for physics learning. This research was conducted at the Laboratory of Physics Education Faculty, University of Muhammadiyah Purworejo with the research subjects of five physics education students. This research is a development research using the ADDIE development model with the Analysis, Design, Development, implementation, and Evaluation stages. Data collection techniques in this study were using validation questionnaires and student responses. The results showed that the developed teaching aid resulted in an error in the acceleration of gravity of 9.59 ± 0.42 m/s2 when the value of h= 0.90 m, 9.61 ± 0.43 m/s2 when the value of h= 1.00 m, and 9.74 ± 0.40 m/s2 when the value of h= 1.10 m, while the results of the validation carried out by media experts obtained a percentage of 93% and material experts 98%. Meanwhile, the results of student responses to teaching aid obtained a percentage of 93.33%. Proximity sensor based free fall motion teaching aid are valid and effective for physics learning.